If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X + 9 = 90 Reorder the terms: 9 + X = 90 Solving 9 + X = 90 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + X = 90 + -9 Combine like terms: 9 + -9 = 0 0 + X = 90 + -9 X = 90 + -9 Combine like terms: 90 + -9 = 81 X = 81 Simplifying X = 81
| 2x+2y+z=11 | | 1-17x+37x=1 | | 19-11/-2 | | 5+2x=-20+5x | | 1/8=z^(6x) | | -14x-25-22=79 | | 14x-25-22=29 | | 18d^5+6d^49+d^3= | | -77=-40m-37m | | 1/3x1/3x1/3x1/3x1/3 | | t-23=78 | | -52+T=4 | | -9(1+7b)=15 | | w+17=19 | | 18x^2-46x-552=0 | | cos(53)=x/7 | | y+50=60 | | 4x+4y=3.5 | | 6y-4=3 | | 9x-3=-33 | | 4m+5n=5 | | 17x+30=-939 | | 2x=6-4x+2-2x | | y=-2E+05ln(x)+1E+06 | | -6--2x/-4 | | 0x+1y=3 | | x=3y^3+4y | | 4.5(r+1)=27-4.5 | | 3m+2n=2 | | Y=-0.5x-3 | | Cos(x+50)=-0.7 | | 3n+8-4n=-17 |